PROXIMAL FEMUR FRACTURE IN OLDER ADULTS: CORRELATION BETWEEN SURGICAL TREATMENT TIME AND MORTALITY - BRUNA GRANIG VALENTE; ALINE CREMASCO ROCHA; HENRIQUE CHIARINI BATISTELLA; CRISTIANE TONOLI VELOZO DE ANDRADE; CARLOS AUGUSTO DE MATTOS; CINTIA KELLY BITTAR (Acta Ortopédica Brasileira)
ABSTRACT Introduction: Osteoporosis impacts public health because of its high morbidity and mortality in older adults and high costs to public funds. Objectives: Analysis of the epidemiological profile, temporal distribution, deaths, and period from low-impact proximal femoral neck fracture to management in older adults people treated at a Tertiary Hospital. Methods: Cross-sectional, descriptive and retrospective study that analyzed 133 medical records involving fractures of the proximal femoral neck due to low-energy trauma from 2017 to 2020. Statistical analysis using the chi-square test, Student’s t-test and Fisher’s exact test. Results: Of the 133 medical records, there was a predominance of females (p < 0.01) with 93 (69.92%). As for age, the average is 79.87±8.23, median 81 years and range from 61-99 years. The months of May, June, and August were dominant (p > 0.05), 15 (11.28%), 10 (7.52%), and 21 (15.79%), respectively. The most common spot (p < 0.001) was the transtrochanteric region 105 (78.95%). In four years, the number of deaths was: 5(20.83%) in 2017, 4(23.53%) in 2018, 8(33.33%) in 2019, 7(10.29%) in 2020,with no significant changes regarding sex (p > 0.05). Conclusion: Most data were consistent with the literature. However, two differ, the transtrochanteric fracture and mortality in 2020. The decrease in deaths in 2020 is mainly due to the new surgery protocol within 48 hours of the fracture. Level Of Evidence IV, Case Series.